2017
DOI: 10.3389/fmars.2017.00129
|View full text |Cite
|
Sign up to set email alerts
|

Primary Life Stage Boron Isotope and Trace Elements Incorporation in Aposymbiotic Acropora millepora Coral under Ocean Acidification and Warming

Abstract: Early-life stages of reef-building corals are vital to coral existence and reef maintenance. It is therefore crucial to study juvenile coral response to future climate change pressures. Moreover, corals are known to be reliable recorders of environmental conditions in their skeletal materials. Aposymbiotic Acropora millepora larvae were cultured in different seawater temperature (27 and 29 • C) and pCO 2 (390 and 750 µatm) conditions to understand the impacts of "end of century" ocean acidification (OA) and oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 113 publications
0
11
0
Order By: Relevance
“…In parallel with these crystallographic structural distortions, we also find some evidence of increased surface etching and roughness (more corrosion) for corals growing within waters with decreasing sw (Supplementary Figure S1). While previous studies have observed marked distortions in coral skeletons and crystallite morphologies in shallow corals growing in undersaturated conditions Tambutté et al, 2015;Foster et al, 2016;Wu et al, 2017), overall skeleton morphology shifts in deep-sea corals are not as obvious. Instead, L. pertusa colonies express only minor outward morphological differences in undersaturated sw conditions with hidden internal crystal morphology toward less ordered, smaller crystallites observable via electron backscatter diffraction (EBSD) (Hennige et al, 2015).…”
Section: Aragonite Mineralogy and Crystallography As A Function Of Sementioning
confidence: 62%
“…In parallel with these crystallographic structural distortions, we also find some evidence of increased surface etching and roughness (more corrosion) for corals growing within waters with decreasing sw (Supplementary Figure S1). While previous studies have observed marked distortions in coral skeletons and crystallite morphologies in shallow corals growing in undersaturated conditions Tambutté et al, 2015;Foster et al, 2016;Wu et al, 2017), overall skeleton morphology shifts in deep-sea corals are not as obvious. Instead, L. pertusa colonies express only minor outward morphological differences in undersaturated sw conditions with hidden internal crystal morphology toward less ordered, smaller crystallites observable via electron backscatter diffraction (EBSD) (Hennige et al, 2015).…”
Section: Aragonite Mineralogy and Crystallography As A Function Of Sementioning
confidence: 62%
“…However, while elevated temperature increased δ 11 B (i.e. increased pH), it did not affect B/Ca or U/Ca (Wu et al, 2017), potentially reflecting the lower degree of thermal stress (culture temperatures were within the seasonal range at the collection site) compared to Foster et al (2015) and/or that [Ca 2+ ] cf played an important role in our Raman data. Nevertheless, our results further highlight that Raman spectroscopy can detect changes in coral calcifying fluid Ar , and that this information is complementary to other analyses, including boron systematics (Sect.…”
Section: Effects Of Temperature and Co 2 On Ar Of Juvenile Acroporamentioning
confidence: 81%
“…Finally, Foster et al (2016) found pitted skeletal surfaces indicative of dissolution, which may have compounded the measured CO 2 effects on calcification and led to their dominance over any apparent effect of temperature in the "+CO 2 + T " treatment. A recent study employing a similar experimental design found that juvenile Acropora B/Ca and U/Ca increased with elevated CO 2 (Wu et al, 2017) based on abiogenic partitioning Holcomb et al, 2016). However, while elevated temperature increased δ 11 B (i.e.…”
Section: Effects Of Temperature and Co 2 On Ar Of Juvenile Acroporamentioning
confidence: 92%
“…We collected 440 spectra from various grains spread onto a glass slide. Although JCp-1 exists in ground form, we note that analysis of intact coral skeletons is also possible (Wall and Nehrke, 2012;Hennige et al, 2014) and that peak widths apparently do not depend on whether the sample is powdered or intact (Zakaria et al, 2008), as long as the grain size exceeds the laser spot size.…”
Section: Raman Measurementsmentioning
confidence: 87%
“…These observations imply that Mg content was not the primary source of lattice defects broadening Raman peaks, an interpretation supported by the absence of a correlation between Mg/Ca and ν 1 FWHM (after accounting for the effect of Ar ; Table 1). The lack of correlation between ν 1 FWHM and position also indicates that ν 1 FWHM was unaffected by crystallite size (Urmos et al, 1991;Zakaria et al, 2008).…”
Section: Controls On Aragonite ν 1 Peak Widthmentioning
confidence: 99%